Perkembangan PT. NPM Padang Panjang 1997-2019 - Yetri Erita; Zul Asri (Jurnal Kronologi, 2020)
This study describes the history of the company in the field of PT. NPM transportation. This type of research includes qualitative research using historical research methods. In historical research there are several steps namely heuristics (collecting data), source criticism (making criticism of existing sources), interpretation (making interpretations related to historical facts) and historiography (writing history). The results of this study explain the development of PT.NPM Padang Panjang as a family company still survives until the third generation. PT. NPM Padang Panjang was established in 1937 by Bahauddin Sutan Barbanso Nan Kuniang. In 1997 the company experienced a setback caused by several factors, namely; (1) the monetary crisis caused capital and spare parts costs to be expensive, so that it affected the increase in transportation prices, (2) the strategy of low-cost aircraft fares since 2002, (3) the existence of travel and minibuses resulted in passengers leaving large buses as a result PT. NPM stopped the AKDP (Inter-City Within Province) route in mid 2008. In the third Angga Vircansa Chairul (2009) PT. NPM experienced a heyday after formalizing tourism transportation in 2012 under the name Vircansa Tour Bous. End of 2018 a fresh breeze for transportation companies after the government implemented an increase in aircraft fares. Until 2019 PT. NPM serves regular transportation and tourism with the latest online ticket and route purchase system to Riau province.